Kaempferol Protects Blood Vessels From Damage Induced by Oxidative Stress and Inflammation in Association With the Nrf2/HO-1 Signaling Pathway - Yao, He; Sun, Jingyu; Wei, Jie; Zhang, Xin; Chen, Bing; Lin, Yajun (Frontiers in Pharmacology, 2020)
In recent years, an increasing number of studies have confirmed that the occurrence and development of vascular pathological changes are closely related to the oxidative stress and inflammatory response of vascular endothelium. Kaempferol is the most common flavonoid compound found in fruits and vegetables. The protection of kaempferol to vascular endothelium was observed in mouse model of vascular injury and its mechanism was explored. Oxidative stress, cardiovascular injury extent, inflammation markers such as NF-κB, TNF-α and IL-6 and Nrf2/HO-1 signaling pathway were studied. The results were demonstrated that kaempferol reduced the H2O2 and paraquat mediated oxidative stress and inflammation in vitro and in vivo, respectively. Kaempferol suppressed the levels of TNF-α and IL-6 and the activation of NF-κB in aortic tissues and HUVECs. Furthermore, kaempferol corrected the levels of antioxidants and elevated the protein levels of Nrf2 and HO-1 in aortic tissues and HUVECs. It can be concluded that kaempferol protects blood vessels from damage induced by oxidative stress and inflammation and Nrf2/HO-1 signaling pathway is involved.